Construction of Fluorinated Propane‐Trap in Metal–Organic Frameworks for Record Polymer‐Grade Propylene Production under High Humidity Conditions - Wang, Yong; Li, Tong; Li, Libo; Lin, Rui‐Biao; Jia, Xiaoxia; Chang, Zeyu; Wen, Hui‐Min; Chen, Xiao‐Ming; Li, Jinping (Advanced materials (Weinheim), 2023)
Propane/propene (C3H8/C3H6) separation is essential in the petrochemical industry but challenging because of their similar physical and chemical properties. Adsorptive separation with C3H8‐selective porous materials can energy‐efficiently produce high‐purity C3H6, which is highly promising for replacing conventional cryogenic distillation but suffers from unsatisfactory performance. Herein, through the precise incorporation of fluorinated functional groups into the confined pore space, a new fluorinated metal–organic framework (FDMOF‐2) featuring the unique and strong C3H8‐trap is successfully constructed. FDMOF‐2 exhibits an unprecedented C3H8 capture capacity of 140 cm3 cm−3 and excellent C3H8/C3H6 (1:1, v/v) selectivity up to 2.18 (298 K and 1 bar), thus setting new benchmarks for all reported porous materials. Single‐crystal X‐ray diffraction studies reveal that the tailored pore confinement in FDMOF‐2 provides stronger and multiple attractive interactions with C3H8, enabling excellent binding affinities. Breakthrough experiments demonstrate that C3H8 can be directly extracted from various C3H8/C3H6 mixtures with FDMOF‐2, affording an outstanding C3H6 production (501 mmol L−1) with over 99.99% purity. Benefiting from the robust framework and hydrophobic ligands, the separation performance of FDMOF‐2 can be well maintained even under 70% relative humidity conditions. With the incorporation of CF3 groups into the confined pore space, the constructed fluorinated metal–organic frameworks (MOFs) exhibit benchmark C3H8/C3H6 separation potential with strong C3H8 binding affinity over C3H6 and exceptional C3H8 uptake capacity. Moreover, the MOFs exhibit high hydrophobicity and good moisture stability, indicating potential applications in efficient C3H8/C3H6 separation under actual conditions with vapour.